Translation the basics - House, Juliane 1942- (London New York Routledge, Taylor & Francis Group, 2018)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- Figures -- Acknowledgements -- Introduction -- Part I Basic issues in the field of translation -- 1 What is translation? -- 2 Translation competence -- 3 Looking at translation from different perspectives -- 4 Culture and ideology in translation -- Part II Some much-discussed concepts in translation theory -- 5 Possibilities and impossibilities of translation -- 6 Universals of translation? -- 7 How do we know when a translation is good? -- Part III Some important new trends in translation studies -- 8 What goes on in translators' heads when they are translating? -- 9 Using corpora in translation studies -- 10 Translation in the age of globalization and digitalization -- Part IV Translation in the real world -- 11 The role of translation in language learning and teaching -- 12 Translation as a social practice in real-life situations -- Glossary -- References -- Index
Keywords: Translating and interpreting; Translation; Translation Studies; Applied Linguistics